Correlation between Neutrophile to Lymphocyte Ratio and D-dimer with COVID-19 Severity - Suhesty, Citra; Dinutanayo, Wimba Widagdho; Tuntun, Maria; Hidayat, Hidayat (Poltekkes Kemenkes Tanjung Karang, 2023)
SARS-CoV-2, a lung-damaging virus, is what causes COVID-19. While a decline in lymphocyte counts suggests immune system harm, a rise in neutrophil counts reflects the severity of the inflammatory response. A high NLR value results from an increase in neutrophils and a decrease in lymphocytes. On the other hand, when plasmin breaks down fibrin to dissolve blood clots, it creates pieces called D-dimers. ARDS is predicted by an elevated D-dimer level. The study's objective was to ascertain how the severity of COVID-19 patients at Dr. H. Abdul Moeloek in 2021 related to NLR and D-dimer levels. Analytical research with a retrospective design is being conducted. The Rank Spearman correlation test and Pearson Chi-Square analyzed medical record data for COVID-19 patients. The study was carried out in Dr. H. Abdul Moeloek in June 2022. 205 COVID-19 patients who underwent NLR and D-dimer testing and were categorized based on the severity of the condition served as the study's subjects. The test findings revealed a substantial connection between NLR and D-dimer (r=0.583), demonstrating a strong and favorable link. NLR and illness severity showed a significant relationship (r=0.49). D-dimer and illness severity also showed a strong connection (r=0.51).